Pencegahan Stunting Melalui Edukasi Manajemen Laktasi - Anggarini, Inge Anggi (Khidmah, 2025)
Children's growth and development is something that must be considered from an early age. Failure of growth and development will have an impact on children's welfare. One of the disorders in children's growth that is currently being widely discussed is stunting. Lactation is the entire breastfeeding process, starting from the production of breast milk to the process of the baby sucking and swallowing the breast milk. Lactation management begins during pregnancy, after delivery and during the breastfeeding period. The scope of lactation management in the postnatal period includes exclusive breastfeeding, breastfeeding methods, expressing expressed breast milk, and providing expressed breast milk. If lactation management is not implemented, it will have an impact on reducing breastfeeding, which can result in an increase in the rate of malnutrition and undernutrition which has the risk of increasing infant mortality. This means that it is very important for mothers to know about lactation management properly and correctly. Education or counseling can be carried out to increase the knowledge or understanding of third trimester pregnant women. The community service method is in the form of education or counseling with the title Stunting Prevention Through Lactation Management Education. This activity will be carried out in December 2024-January 2025 at PMB Herasdiana Palembang. During this 2 month period, several stages of preparation were carried out and coordinated with related parties and provided education to mothers at PMB Herasdiana Palembang